Facets of the American South: Essays on a Peculiar South (2024)
This collection of essays brings together an international group of scholars who discuss various facets of the American South in popular culture, literature, the arts, and throughout history. It includes reflections on place, on the importance of memory in shaping individual identity, and on race, class and gender. All the contributions confirm Howard’s Zinn’s idea that the South “is not damnable, but marvelously useful, as a mirror in which the nation can see its blemishes magnified, so that it will hurry to correct them.” This volume sheds light on the “marvelous” sides of the South though it does not overlook its darker ones, thus making it possible to better understand this peculiar region.Aquest recull d’assajos reuneix un grup internacional d’estudiosos que analitzen diverses facetes del Sud dels Estats Units en la cultura popular, la literatura i les arts al llarg de la història. Inclou reflexions sobre el lloc, sobre la importància de la memòria en la conformació de la identitat individual, i sobre raça, classe social i gènere. Totes les contribucions confirmen la idea d’Howard Zinn que el Sud “no és condemnable, sinó meravellosament útil, com a espill en el qual la nació pot veure magnificades les seues imperfeccions, perquè s’afanye a corregir-les”. Aquest volum aporta llum sobre els aspectes “meravellosos” del Sud, encara que no passa per alt els seus aspectes més foscos, el que permet comprendre millor aquesta peculiar regió.
Keywords: essays; USA; popular culture; literature; arts